Benin : Third Review Under the Extended Credit Facility Arrangement. (IMF Staff Country Reports; Country Report ;, 2012)
This papers discusses Benin's third review under the Extended Credit Facility Arrangement. The re-election of the President and the regained majority in Parliament have provided a window of opportunity for reforms. All performance criteria and most quantitative targets have been met, but progress in implementing structural reforms was mixed. The introduction of critical customs reforms met with strong initial resistance, leading to a sharp fall in customs revenue in the second half of 2011. The financial system remains sound, but supervision needs to be strengthened.